Serum soluble CD26 levels: diagnostic efficiency for atopic dermatitis, cutaneous T‐cell lymphoma and psoriasis in combination with serum thymus and activation‐regulated chemokine levels. (14th November 2011) - Miyagaki, T.; Sugaya, M.; Suga, H.; Morimura, S.; Kamata, M.; Ohmatsu, H.; Fujita, H.; Asano, Y.; Tada, Y.; Kadono, T.; Sato, S.
Abstract: Background CD26 is a multifunctional type II transmembrane glycoprotein, which also exists as a secreted isoform, soluble CD26 (sCD26). The CD26 expression on circulating T cells is decreased in some skin diseases such as cutaneous T‐cell lymphoma (CTCL) and psoriasis. It remains to be determined whether sCD26 can be used as a marker of skin diseases or not. Objective To investigate utility of sCD26 as a diagnostic marker of skin diseases in combination with thymus and activation‐regulated chemokine (TARC). Methods Serum sCD26 levels were measured using enzyme‐linked immunosorbent assay in 130 participants including 32 patients with atopic dermatitis (AD); 45 patients with CTCL; 26 patients with psoriasis; and 27 healthy controls. Results Serum sCD26 levels in patients with CTCL and psoriasis (162.1 ± 80.2 ng/mL and 125.4 ± 82.1 ng/mL respectively) were significantly lower than those of healthy controls (392.6 ± 198.7 ng/mL; P < 0.01 and 0.01 respectively). In patients with CTCL, serum sCD26 levels of patients with advanced stage were 135.0 ± 51.5 ng/mL and they were significantly lower than those with early stage (193.1 ± 96.0 ng/mL; P < 0.05). When we used serum sCD26 and TARC levels for diagnostic criteria, sensitivity, specificity, positive predictive value and negative predictive value for AD, CTCL and psoriasis were 65.2–73.7%, 81.4–97.6%, 65.2–94.4%, and 81.4–88.9% respectively. Conclusion Serum sCD26 levels, combined with serum TARC levels, are helpful in diagnosis of AD, CTCL and psoriasis.